PC.77 Sedation and analgesia for neonates in NICUs across the United Kingdom: The Europain survey. (9th June 2014) - Carbajal, R; Courtois, E; Eriksson, M; Lagercrantz, H; Boyle, EM
Abstract : Background: Pain and stress induced by mechanical ventilation, invasive procedures, or painful diseases supports the use of sedation/analgesia (S/A) in newborns admitted to Neonatal Units (NNUs). To date, these practices have not been studied on a large scale. Objective: To determine current clinical practices regarding the use of S/A drugs in NNUs across the United Kingdom (UK). Design/Methods: A European epidemiological observational study on clinical practices regarding bedside use of S/A collected data for all neonates in participating NNUs until the infant left the unit (discharge, death, transfer) or for up to 28 days. Data collection occurred via an online database for 1 month at each NNU. Neonates up to 44 weeks gestation were included. Results: From February 2013 to May 2013, 66 UK NNUs collected data on 2691 eligible neonates. Of these, 713 received tracheal ventilation and 1978 had spontaneous breathing or non-invasive ventilation. The median (IQR) gestational age of ventilated neonates [32.1 (27.9–38.6)] was lower than for non-ventilated neonates [37.0 (34.1–39.7), p < 0.001]. Overall, more ventilated neonates [83.0% (n = 592)] received S/A drugs than non-ventilated neonates [7.4% (n = 147); p < 0.001]. The table shows S/A drugs used in ventilated neonates. Conclusions: Most ventilated but few non-ventilated neonates receive S/A therapy in UK NNUs. Wide variations in rates of S/A use and drugs used exist among centres.